Immune checkpoint blockade and head and neck cancer - Schoenfeld, Jonathan (Henry Stewart Talks, 2015)
Immune checkpoint blockade and head and neck cancer, History of immunotherapy, The immune system and cancer, Introduction to checkpoint blockade, Introduction to head and neck cancers, Head and neck cancers as an immunologic target, Preliminary evidence for checkpoint blockade, Ongoing / future studies
Archived at 2023/06/29